The effect of nanoparticles composition ratio on dynamic viscosity of Al2O3-TiO2-SiO2 nanofluid - Ramadhan, Anwar Ilmar; Wan Azmi, Wan Hamzah (Elsevier Ltd, 2021)
In recent years, research has concentrated on improving the thermo-physical properties of a single component nanofluid. As a result, hybrid or composite nanofluids are being developed to enhance heat transfer performance. Dynamic viscosity of Al2O3-TiO2-SiO2 nanoparticles suspended in W/EG mixture (60:40) in various composition ratios were investigated for a constant volume concentration of 3.0%. Experiments were performed for the mixing ratio (CR 1, CR 2, CR 3, CR 4, CR 5, CR 6) of Al2O3-TiO2-SiO2 nanofluids with temperature conditions of 30, 40, 50, 60 and 70 C. The dynamic viscosity measurements were undertaken at temperatures between 30 and 70 C using Brookfield LVDV-III Ultra Rheometer. The experimental results reveal that the mixing ratio of CR 3 (20:64:16) is considered the best ratio with the lowest relative viscosity when compared to CR 1, CR 2, CR 3, CR 4, CR 5, and CR 6. As a result, the mixing ratio of three distinct nanoparticles namely TiO2, SiO2, and Al2O3 became the control and performance factors in the present study. When compared to other mixing ratios, the CR 3 is raising the relative viscosity yields the smallest increment of 2.35-3.08 times higher than based fluid. It was recommended to determine the lowest dynamic viscosity of Al2O3-TiO2-SiO2 nanofluids or tri-hybrid nanofluids for the lowest potential pressure drop in heat transfer applications.